THE INFLUENCE OF VILLAGE OFFICIAL COMPETENCE ON THE QUALITY OF PUBLIC SERVICES IN AMPUKUNG VILLAGE, KELUA SUB-DISTRICT, TABALONG REGENCY - Akhmad Berkatillah; Siti Mujahadah (PPPM STIA Amuntai, 2025)
This research was conducted in Ampuung Village, which is located in Kelua District, Tabalong Regency, found several problems such as village officials do not have sufficient knowledge and skills to carry out their duties and responsibilities, many still have not mastered basic technical skills such as administrative management and information technology, lack of good work attitudes such as discipline and integrity, and minimal ability in providing services to the community, this has an impact on public services that are not on schedule, delays in making important letters or changing information, village employees seem slow in responding to requests or complaints from the public, officials are sometimes unable to provide clear explanations regarding service procedures. The method used in this study is quantitative descriptive, the number of samples is 97 respondents and analyzed using SmartPLS version 4. The results of the study show that Village Apparatus Competence has an influence on the Quality of Public Services with a P Value of 0.000 <0.05 and with a t value of 27,810 (> t-table 1.984), this means that the Hypothesis (Ha) is accepted. The magnitude of the influence is known from the structure of the research model which can be accepted based on the R-Square value, it is known that Competence influences the Quality of Public Services by 0.912 or 91.2%, the remaining 8.8% are other factors that also influence Employee Performance, including errors.